In-Hospital Peak Glycemia in Predicting No-Reflow Phenomenon in Diabetic Patients with STEMI Treated with Primary Percutaneous Coronary Intervention - Fang Liu; Rui Huang; Ya Li; Surui Zhao; Yue Gong; Zesheng Xu (Journal of Diabetes Research)
Although percutaneous coronary intervention (PCI) significantly improves the prognosis for myocardial infarction, the no-reflow phenomenon is still the major adverse complication of PCI leading to increased mortality, especially for the patients with ST-segment elevation myocardial infarction (STEMI) combined with diabetes. To reduce the occurrence of no-reflow, prognostic factors must be identified for no-reflow phenomenon before PCI. A total of 262 participants with acute STEMI and diabetes were recruited into our cardiovascular center and underwent primary PCI for the analyses of prognostic factors of no-reflow. The patients were divided into two groups according to thrombolysis in myocardial infarction (TIMI): the normal flow and no-reflow groups, and related factors were analyzed with different statistical methods. In the present investigation, the in-hospital peak glycemia was significantly higher in the no-reflow group than the normal flow group, while more narrowed vessels, higher level of initial TIMI flow, were observed in the patients of the no-reflow group. A multivariate logistic regression analysis further demonstrated that peak glycemia was an independent predictor for no-reflow in the diabetic patients with STEMI. Our data indicated the importance of the proper control of glucose before PCI for the diabetic patients with STEMI before PCI to reduce the occurrence of the no-reflow after operation.